(untitled) (Cuidado y Ocupación Humana, 2023)
Objective: to determine the relationship between transformational leadership of the nursing professional and the dimensions of organizational commitment in the E.S.E Hospital Manuela Beltrán. Method: descriptive cross-sectional study in which 100 nursing professionals participated, data collection was carried out using the organizational commitment scale of Meyer and Allen (1997), adapted and validated in the Spanish version in Mexico and Spain by Luis Arciniega and Luis Gonzáles (2006) and the Multifactorial Transformational Leadership questionnaire (short MLQ-5S). Data treatment was performed using Excel and descriptive statistics were executed using the IBM SPSS Statistics software. Results: It was possible to show that there is a low and highly significant positive relationship between transformational leadership and continuity commitment (Rho = -0.110, p> 0.05) and a very significant positive relationship between transformational leadership and normative commitment ((Rho = 0.713, p = 0.000). Conclusions: According to the statistical results, there is a significant relationship between transformational leadership and normative and continuous organizational commitment in nursing professionals.